Decrease In Organic Substances And H2S With Peat Water Treatment Continuous System For Media Life Goldfish (Cyprinus Carpio) - Sunawiruddin Hadi; Budijono '; M. Hasbi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2014)
This study was conducted in April-May 2014 Tarai River Tarai Bangun Village Districts Tambang District Kampar in Riau Province. The purpose of this study were to reduce organic matter and H2S. The method was used in experimental to know a combined of tank unit and filtration. Results of organic matter during the observation reaches 93.47% effectivity and H2S with 96.8% effectivity. While the other parameters such as pH 7, temperature 28 0C, and DO 5 mg / l. in the control of organic matter and H2S quality standard that is still above organic substances and to H2S with an. Examination on fish survival rate in the processed water continuous peat at the end of the observation system has been able to support fish life test. Where to carp (Cyprinus carpio) survival achieve 100%. While examination to control all test fish death until the end of the observation.Keywords : organic matter, H2S, Water Peat, goldfish habitat